Perinatal outcome of 50 cases of abnormal umbilical artery Doppler ultrasound study (Journal of Dhaka National Medical College & Hospital, 2015)
Objective : The main objective of this study was proper detection of the compromised fetus to allow for timely intervention and to reduce perinatal morbidity and mortality.  Materials and Methods  This is a cross sectional descriptive type of study which was conducted in the department of Obstetrics and Gynaecology in DNMCH from January 2006 to December 2006.  Results :  In this study gestational age was determined by clinical examination, LMP and USG. There was a high incidence of caesarean section in this study. The reason of this high incidence was due to obstetrics indications like severe preeclampsia, severe PIH, Oligohydramnios, indications of emergency caesarean section was (58.97%). High risk cases were decided to terminate by Umbillical artery Doppler study. In the present study in most cases delivery occurs within 3-4 days of the last test. The prevalence of perinatal death in fetuses with absent or reversed end diastolic flow velocity was 40%. 5 minute Apgar score